Inactivation of maize transposon Mu suppresses a mutant phenotype by activating an outward-reading promoter near the end of Mu1. - Barkan, A (1991)
We described previously a mutation in maize, hcf106, caused by the insertion of a Mu1 transposon. When the Mu transposon system is in an active phase, hcf106 conditions a nonphotosynthetic, pale green phenotype. However, when the Mu system is inactive (a state correlated with hypermethylation of Mu elements), the plant adopts a normal phenotype despite the continued presence of the transposon within the gene. The molecular mechanisms that mediate this suppression of the mutant phenotype have now been investigated. We show here that the Mu element responsible for the hcf106 lesion lies within sequences encoding the 5'-untranslated leader of the Hcf106 mRNA. When the Mu transposon system is active, this insertion interferes with the accumulation of mRNA from the hcf106 allele. However, when Mu is inactive, mRNA similar in size and abundance to that transcribed from the normal allele accumulates. These transcripts initiate at many sites throughout a 70-base-pair region, within and immediately downstream of the Mu1 insertion. Thus, an unusual promoter spanning the downstream junction between Mu1 and Hcf106 substitutes for the normal Hcf106 promoter but only when Mu is inactive. The pattern of mRNA accumulation in different organs and in response to light suggests that the activity of this promoter is conditional not only upon the phase of Mu activity, but also upon signals that regulate the normal Hcf106 promoter.